Impact of access to ICT on regional economic growth in Kazakhstan - Nurbatsin, A.; Kireyeva, A. (Journal of Economic Research & Business Administration, 2020)
This article examines the impact of access to information and communication technologies (ICT) in organizations on regional economic growth in Kazakhstan. The main objective of the study is to compare regions with high, medium and low levels of regional development. Data were collected for the period 2007-2018 for all 16 regions of the country. Internet access in organizations, the number of computers and landlines were considered as ICT, and the main indicator of regional development was taken as the gross regional product (GRP) of the regions of Kazakhstan. POLS (pooled ordinary least squared) – the combined least squares method (for panel studies), FE (fixed effects) – the method with fixed effects, RE (random effects) – the method with random effects, and IV (instrumental variables) – the method with instrumental variables were used to create a regression model with high reliability. The region’s innovation activity for the number of computers in organizations was adopted as an instrumental variable. The article presents the results of a regression model with the division of regions with high, medium and low development and their analysis. In addition, the results were presented for splitting into sub-periods of 2007-2013 and 2014-2018 years. Significant differences between groups of regions of Kazakhstan were not revealed as a result of this study.